Fischer–Helferich glycosidation mechanism of glucose to methyl glycosides over Al-based catalysts in alcoholic media. Issue 36 (17th August 2022) - Yu, Mengting; Li, Yao; Zhang, Cheng; Luo, Huaying; Ge, Chengsheng; Chen, Xiaobin; Fu, Lanlan; Ju, Zhaoyang; Yao, Xiaoqian
Abstract : The reaction mechanism of conversion of glucose to methyl glycosides (MDGP) catalyzed by Al-based catalysts through Fischer–Helferich glycosidation has been probed by DFT calculations. Abstract : The Fischer–Helferich glycosidation reaction is generally the initial step in the conversion of glucose to levulinate in alcohol media. However, the relevant molecular mechanism catalyzed by Al-based catalysts is still not well understood. In this work, the reaction mechanism of the glycosidation from glucose to methyl glycosides catalyzed by Al 3+ coordinated with methanol/methoxyl was investigated through density functional theory (DFT) calculations. The whole reaction process includes ring-opening, addition, and ring-closure events. The addition of methanol to the ring-opening structure of glucose makes the electronegativity of C1 site stronger to proceed with the following ring-closure reaction. Among the 28 kinds of ways of ring-closure reaction, the most preferred way is to close the loop through the six-membered ring (O5–C1) to generate methyl glucoside (MDGP). The rate-determining step is the ring-closure and the Al 3+ shows a great catalytic effect which is mainly reflected in coordinating with the solvents to transfer protons. The results would be helpful to understanding the Fischer–Helferich glycosidation mechanism catalyzed by Al-based catalysts and comprehend the conversion of glucose to high value-added chemicals.